Nutritional aspects of studying vegetable marrows and Zucchini fruits - Iosipenko, Olena; Kyslychenko, Viktoriia; Novosel, Olena; Zhuravel, Iryna; Burda, Nadiya; Popik, Andriy (Annals of Mechnikov’s Institute, 2025)
Introduction. Nutrition forms the foundation of human life and is one of the most vital factors in reducing the risk of developing nutrition-related diseases. It helps ensure active longevity and supports the body’s adaptive potential. Poor nutrition contributes to the development of diseases such as atherosclerosis, arterial hypertension, hyperlipoproteinemia, type II diabetes mellitus, obesity, osteoporosis, gout, gallstone disease, iron deficiency anemia, and others. Plant-based foods, including vegetable marrows and zucchini, play a key role in providing essential nutrients in the diet. Vegetable marrows (Cucurbita pepo L. var. giromontina Alef.) and zucchini (Cucurbita pepo L. var. cylindrica Paris) are annual herbaceous bushy plants from the Cucurbitaceae family, subspecies of the common pumpkin (Cucurbita pepo L.). The fruit of vegetable marrows and zucchini is a multi-seeded false berry. Different plant varieties vary in fruit shape, skin surface, and skin and flesh color; they lack a flesh cavity. The quality of raw materials is regulated by DSTU 318-91 "Fresh vegetable marrows. Technical conditions," which states that 8-12-day-old fruits with unformed seeds up to 25 cm long and up to 8 cm in diameter are used. It is known that vegetable marrows and zucchini fruits are sources of phenolic compounds, carbohydrates, vitamins, and minerals. These nutrients confer antioxidant, hypoglycaemic, anabolic, cytotoxic, immunomodulatory, diuretic, and choleretic effects, among others. Vegetable marrows seeds contain fatty oil, which is used similarly to pumpkin seed oil. Vegetable marrows fruits are recommended to be included in the diets of children—especially infants—elderly individuals, and those with digestive or metabolic issues. The aim of the study was to investigate the chemical composition (fatty acids, amino acids, macro- and microelements) of Aspirant vegetable marrows and Zolotinka zucchini fruits to determine their potential use as a source of macro- and micronutrients. Materials and methods. The objects of the study were vegetable marrows and zucchini fruits, which were dried by convection to an air-dry state and ground. The resulting light cream-colored powders were analyzed to determine the qualitative composition and quantitative content of fatty acids using gas chromatography-mass spectrometry, amino acids through ion-exchange liquid-column chromatography, and mineral compounds by atomic emission spectroscopy. Results and discussion. Nine fatty acids were identified and quantified in vegetable marrows and zucchini fruits, with six being unsaturated and three saturated. Their acid profile was consistent in composition. Quantitatively, the fatty acids in zucchini fruits were predominant. Unsaturated fatty acids primarily dominated the overall fatty acid composition of the studied raw materials, with their content nearly twice as high as that of saturated fatty acids. Linolenic acid was the most abundant in both fruits, comprising more than 38%, while linoleic acid was about half as much, at 16-19%. Among saturated fatty acids, palmitic acid was the most prevalent, making up over 21% of the raw material. Conclusions. The qualitative composition and quantities of macro- and micronutrients (fatty acids, amino acids, macro- and microelements) in Aspirant vegetable marrows and Zolotinka zucchini fruits have been determined. The results show that the studied raw materials are sources of essential polyunsaturated fatty acids, essential amino acids, macro- and microelements that are important for health. These nutrients have a preventive effect against coronary heart disease, metabolic syndrome, and other chronic illnesses. The experimental data obtained allow us to evaluate the nutritional potential of certain varieties of vegetable marrows and zucchini, opening up opportunities for their future use in pharmacy.